2016
DOI: 10.1038/srep26924
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of the Interaction of Veratrum Nigrum with Panax Ginseng on Estrogenic Activity In Vivo and In Vitro

Abstract: Panax ginseng (GS) and Veratrum nigrum (VN) are representative of incompatible pairs in “eighteen antagonistic medicaments” that have been recorded in the Chinese medicinal literature for over 2,000 years. However, evidence linking interference effects with combination use is scare. Based on the estrogen-like effect of GS described in our previous studies, we undertake a characterization of the interaction on estrogenic activity of GS and VN using in vivo models of immature and ovariectomized (OVX) mice and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…First, previous studies have reported that large doses of GS inhibit the activity of mice (48,49). Second, aside from their appetite, mice exhibit reduced consumption and exercise levels naturally (50,51). in conclusion, GS increase the basal metabolic rate of mice to enhance fat mobilization and thereby reduce weight.…”
Section: Effect Of Gs On Metabolic Measuresmentioning
confidence: 78%
See 1 more Smart Citation
“…First, previous studies have reported that large doses of GS inhibit the activity of mice (48,49). Second, aside from their appetite, mice exhibit reduced consumption and exercise levels naturally (50,51). in conclusion, GS increase the basal metabolic rate of mice to enhance fat mobilization and thereby reduce weight.…”
Section: Effect Of Gs On Metabolic Measuresmentioning
confidence: 78%
“…china was the first country globally to use and record ginseng in medical literature. Ginseng has been recorded in chinese medical literature for >2,000 years (51). GS are regarded as the main active ingredient in ginseng, thus becoming the point of focus in research (52).…”
Section: Discussionmentioning
confidence: 99%
“…However, based on the records of Chinese medical applications, the use of ginseng together with some specific herbs such as Veratrum nigrum L. should be avoided altogether as it can reduce or even reverse the therapeutic function of ginseng. Such interactions have recently been supported by scientific evidence [76]. There are also some other descriptions of interactions between ginseng and food in Chinese practice, for instance, the consumption of radish (Raphanus sativus L.) may reduce the nourishing effect of ginseng.…”
Section: Interactions Of Ginseng With Other Drugsmentioning
confidence: 80%
“…Inhibits production of NO, ROS, TNF-α; inhibits expression of NF-κB, IRF-1, STAT1, JAK1, STAT1, STAT3, ERK [74,76]…”
Section: Rh1mentioning
confidence: 99%
“…Aconite Lateralis Radix Praeparata (Fuzi) and Pinelliae Rhizoma (Banxia) are representative of incompatible pairs recorded in “the eighteen antagonisms”, a special rule for TCM incompatibility in formulas, which suggests strictly compatibility prohibition in clinical prescriptions because mutual antagonism results in an undesirable consequence [ 3 , 5 ]. However, coadministration of the two herbs has been used in many clinical formulas for several centuries.…”
Section: Introductionmentioning
confidence: 99%